Defining screening criteria and ranking in-row and inter-row cover crops for irrigated vineyards using a hybrid AHP–TOPSIS model - Sharifi, Mehdi; Sayyad, Abbas; El Sayed, Eman (Frontiers in Plant Science, 2026)
Cover crops are increasingly important in sustainable vineyard management, yet species selection remains site-specific and challenging. We evaluated candidates in two commercial organic vineyards in the semi-arid Okanagan Valley, British Columbia—CFF (13-year Merlot) and KOW (10-year Zweigelt)—using a hybrid multicriteria decision analysis (MCDA) [Analytic Hierarchy Process–Technique for Order Preference by Similarity to Ideal Solution (AHP–TOPSIS)]. Nine in-row and 15 inter-row treatments (annuals and perennials) were evaluated in the 2019 growing season. Field measures included biomass, ground cover, interference with the fruiting zone, invasiveness, pest/disease effects, drought and winter tolerance, and traffic tolerance. In both vineyards, risk of invasiveness (~43–60%) and interference with fruiting zones (~30%) were the most influential criteria. The top under-vine annuals were Lens culinaris (spring lentil), Brassica napus cv. Winfred, and Brassica rapa (purple-top turnip) with high relative closeness (RCi = 0.87–0.96). Among perennials, Ladino Trifolium repens cv. Crescendo ranked the highest (RCi ~ 0.84), supporting its use as a durable under-vine cover. For inter-rows, Pisum sativum + Secale cereale (pea–rye) led at CFF (RCi = 0.89) and placed second at KOW, Trifolium incarnatum ranked second at CFF (RCi = 0.83), and Trifolium alexandrinum led at KOW (RCi = 0.94). Other annual clovers were intermediate (RCi = 0.79–0.88), performing best on finer-textured, cooler, moister sites. The leading perennial inter-row mix was Lolium perenne + Raphanus sativus var. longipinnatus (tillage radish; RCi = 0.94), followed by a Festuca spp. mix (RCi = 0.65–0.69). This MCDA delivers clear, literature-aligned rankings and a data-driven framework to guide regionally adapted cover-crop choices and future web-based decision tools.